2015
DOI: 10.1021/acs.jpcb.5b09859
|View full text |Cite
|
Sign up to set email alerts
|

13C NMR Studies, Molecular Order, and Mesophase Properties of Thiophene Mesogens

Abstract: Three-ring mesogens with a core comprising thiophene linked to one phenyl ring directly and to the other via flexible ester are synthesized with terminal alkoxy chains to probe the mesophase properties and find the molecular order. The phenyl thiophene link in the core offers a comparison of the mesophase features with the molecular shape of the mesogen. The synthesized mesogens display enantiotropic polymesomorphism and accordingly nematic, smectic A, smectic C and smectic B mesophases are perceived depending… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(59 citation statements)
references
References 61 publications
1
58
0
Order By: Relevance
“…Significant effort has been made to investigate thiophene‐based mesogens by our group using 13 C NMR measurements . It was well recognized that the replacement of phenyl ring with thiophene in mesogen results in decrease of melting point, increase of optical anisotropy, reduction in viscosity, promotion of negative dielectric anisotropy, and fast switching times .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Significant effort has been made to investigate thiophene‐based mesogens by our group using 13 C NMR measurements . It was well recognized that the replacement of phenyl ring with thiophene in mesogen results in decrease of melting point, increase of optical anisotropy, reduction in viscosity, promotion of negative dielectric anisotropy, and fast switching times .…”
Section: Resultsmentioning
confidence: 99%
“…The usefulness of the 2D-SLF spectroscopy for providing information on the molecular order and thereby on the dynamics and the topology of mesogens has been demonstrated. The combination of 13 C chemical shifts and 13 C─ 1 H dipolar [51] MN-2 SmA Veeraprakash et al [83] MN-3 SmC, SmB Veeraprakash et al [83] MN-4 Nematic, SmA, SmC Veeraprakash et al [82] MN-5 SmA Pratap et al [64] MN-6 SmA Pratap et al [64] MN-7 Nematic Santhosh Kumar Reddy et al [60] MN-8 SmC, SmB Santhosh Kumar Reddy et al [60] Abbreviations: SmA, smectic A; SmB, smectic B; SmC, smectic C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that in 2D SLF experiment, except for the isolated C−H pair, the dipolar coupling information needs to be extracted from the experimental dipolar oscillation frequency for carbons that are coupled to more than one proton. 43,44 By implementing the established procedure, [16][17][18][19][20]41,42,45 for a given ring, that is, phenyl or thiophene ring, the dipolar couplings are related to the main order parameters, namely, S zz and S xx −S yy by the following equation 46,47 (1)…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Samulski et al previously showed that the replacement of a phenyl ring with a thiophene in the core profoundly influences the molecular topology as well as the mesophase transitions. , Thus the dramatic change in the mesophase transitions and molecular shape in phenyl thiophene versus all phenyl ring mesogens is attributed to the geometry of the respective thiophene and phenyl rings. , Accordingly, the core unit consisting of irregular pentagon of thiophene and regular hexagon of phenyl profoundly influences the overall molecular shape of the mesogen . We have been exploring the molecular structure and topology of thiophene mesogens in liquid-crystalline phases by high-resolution solid-state 13 C NMR spectroscopy. This technique is particularly suitable for probing the structure at atomistic level because the orientational constraints of thiophene as well as phenyl rings are accessible through 13 C– 1 H dipolar couplings from 2D separated local field (SLF) NMR experiments. As a consequence, the derived orientational constraints of the constituent moieties from 2D experiments can be correlated to functional properties of the mesogen.…”
Section: Introductionmentioning
confidence: 98%